KAJIAN BEBERAPA VARIETAS TEBU PADA AGROEKOSISTEM LAHAN KERING DI KABUPATEN DOMPU-NTB - Sudarto Sudarto (CROP AGRO, Scientific Journal of Agronomy, 2020)
Dompu Regency is one of the national sugarcane development areas, which supports the target of consumption sugar self-sufficiency and then increases to national sugar self-sufficiency. In 2014, the central government has collaborated with the Dompu district government to expanding intensification of sugarcane farming, especially on dry land / moor on ​​1,000 ha of area. Shifting the function of the sugarcane development land occurs because the conversion of technical irrigation rice fields into industrial buildings and other infrastructure. To support the development of sugar cane on dry land, then the way to increase the productivity of sugarcane are by using new superior varieties of sugar cane with high production potential and high yield. The assessment of several sugar cane varieties has been implemented in Beringin Jaya village, Pekat sub-district, Dompu, in 2016 with the aim to finding out the potential production and yield of several sugar cane varieties on dry land. The design used was a Randomized Block Design, with 4 replications. The varieties tested were 5 types, that is: PS 862 (comparator); BL; PSJT 941; PS 881 and PS 851. The size of each plot is 13 x 5 m, planting distance is 130 x 50 cm (single pitch). Parameters observed: plant height (cm), stem diameter (cm), number of sections, number of tillers, brix (%), production (t / ha), and estimated yield (%). Observations made before the harvest (age 10 months). Data were analyzed using analysis of variance (Anova) DSAASTAT software Version 1.101, Italy and if there were significant differences, the analysis was continued with the LSD test at 5% level. The results of the study showed that the analysis of plant height, stem diameter and production of the tested varieties were not significantly different, whereas the number of sections, number of tillers, brix and yield estimates were significantly different. PS 851 variety produced the highest yield of 9.27% ​​and was followed by PS 862 (9.06%), PS 881 (8.46%), PSJT (98.11%), and BL (8,08%). The results of farmers' preferences on agronomic characteristics and yield components of sugarcane varieties tested on dry land showed that farmers were more dominant in choosing PS 851, PS 862 and PSJT 941 varieties.